P127 Is FeNO a useful measure in the assessment of acute exacerbations of COPD?. (12th November 2019) - Price, A; Linacre, E; Gill, N; McDonnell, L; Jackson, D; Dewar, A
Abstract : Introduction and objectives: FeNO is a quantitative, non-invasive biomarker of type 2 airway inflammation and is an established tool in the assessment of patients with asthma. 1 However, the role of FeNO in COPD care remains unclear, despite up to 30% of patients with COPD having evidence of eosinophilic airways inflammation. 2 We investigated whether FeNO measurement is feasible in patients with an acute exacerbation of COPD (AECOPD) and whether it was elevated in any patients with a low blood eosinophil count. Methods: FeNO testing was performed on patients who presented to hospital with an AECOPD. Patients with a prior diagnosis of asthma were excluded. FENO was recorded at the patient's bedside within 24 hours of arrival. If the patient was unable to record a result after 5 attempts, they were deemed unable to perform the test. Blood eosinophil count was measured as part of routine blood tests. Time of corticosteroid administration, highest blood eosinophil count in the preceding 2 years, exacerbation history, oral corticosteroid and inhaled steroid exposure were recorded from integrated electronic records. Results: 61 patients were admitted with AECOPD and met criteria for testing. 43 (70%) patients were able to perform the test. FeNO results are reported for each category in Table 1. Six (14%) patients did not have a blood eosinophils ≥0.3 on presentation but were noted to have raised FeNO. 5 (23%) of these had no raised eosinophils over the last 2 years. Conclusions: FeNO test appears feasible in patients with AECOPD, with 70% of patients able to perform the test. 23% of patients with an AECOPD had an elevated FeNO despite blood eosinophils of <0.3. Further research is required to understand the utility of FeNO in the acute setting of a COPD exacerbation and whether it can be used to guide therapy or predict outcomes. References: Dweik RA, et al . An official ATS clinical practice guideline: interpretation of exhaled nitric oxide levels (FeNO) for clinical applications. Am J Respir Crit Care Med 2011;184:602–615. Gareth Hynes, et al . ERJ 2015;46:PA3993; doi: 10.1183/13993003.congress-2015.PA3993.